Simulation Model of Single-Phase AC-AC Converter by Using MATLAB - Dina Harith Shaker; Salam Waley Shneen; Fatin Nabeel Abdullah; Ghada Adel Aziz (Journal of Robotics and Control (JRC), 2022)
The current research sheds light on the electronic power devices that work as transformers and are named according to the function. A model of a single-phase transformer AC-AC type with half-wave and full-wave quality has been proposed. Its output is controlled by power, voltage and current, which is considered an input to the load. The fixed input transformer has a variable output according to the required power, voltage and current. Inverters of this type have so many uses that they are used in many different applications, including industrial, induction motor speed control, military, medical and household, including low-light circuits, among others. A simulation involving different types of single-phase AC transformers is proposed. The models were built in two ways, the first using a diode as an electronic switch, and the second using a thyristor. Different values for the load were chosen by adopting three values of 30 ohms, 40 ohms, and 50 ohms. An alternating power supply with an RMS value of 222 volts. Simulation was carried out after modeling to test the performance of the proposed transformer and its various modes of operation. Simulation models confirmed and reinforced the working theories of the proposed structures. From the results, we can reach the possibility of changing the voltage and power values using the electronic transformer by using the frequency of closing and opening the electronic keys within specific periods according to the proposed model, which can be represented or modified.